The African American Sonnet : A Literary History - Müller, Timo (Book collections on Project MUSE., 2018)
"The African American Sonnet: A Literary History draws on extensive archival research to offer the first comprehensive survey of this genre. Timo Müller adopts sonnets to open up fresh perspectives on African American literary history, complicate previous accounts of its development, and offer new insight into key phases. He examines the subversion of genteel conventions in the late nineteenth century, the ambivalences of Harlem Renaissance protest, the range of transnational conversations in the 1930s, the innovations of black vernacular modernism, the creative margins of the Black Arts movement, and the many shapes of black experimental poetry today. In this study, Müller focuses on poets such as James Weldon Johnson, Paul Laurence Dunbar, Claude McKay, Countee Cullen, Langston Hughes, Gwendolyn Brooks, Margaret Walker, and Rita Dove. Since the Romantics, the sonnet has broken national, cultural, and geographic boundaries. While European in origin, the sonnet has been reimagined by poets across the world, and its form has been a vehicle for literary legitimacy as well as a subversion of the European literary tradition by poets otherwise excluded. This book examines the inventive strategies African American poets devised to occupy and reshape a form overwhelmingly associated with Europe. In the tightly circumscribed space of sonnets, these poets mounted evocative challenges to the discursive and material boundaries they confronted."--Provided by publisher.